Development and optimisation of a new linear programming model for production/distribution network of an edible vegetable oils manufacturer. Issue 1 (16th May 2011) - Paksoy, Turan; Cavlak, Emine B.
Supply Chain Management (SCM) concerns with the optimal flow of materials and knowledge through overall production/distribution system from raw material suppliers to the last customers. Design and optimisation of production/distribution networks which includes sub problems such as assigning the numbers and the locations of entities of the network and determining the amount of physical distribution among the entities, has a strategic role in SCM. In this study, a novel linear programming model is developed for the production/distribution network of an edible vegetable oils manufacturer. The proposed model is solved and numerical results are analysed for various scenarios in order to identify some managerial insights.